The potential for segmentation of the retail market for electricity in Ireland - Marie Hyland; Eimear Leahy; Richard S. J. Tol (The Economic and Social Research Institute (ESRI), 2012)
We estimate the gross margin that is earned from the supply of electricity to households in Ireland. Using half hourly electricity demand data, the system marginal price (also called the wholesale price) and the retail price of electricity, we analyse how the gross margin varies across customers with different characteristics. The wholesale price varies throughout the day, thus, the time at which electricity is used affects the gross margin. The main factor in determining gross margin, however, is demand. The highest gross margins are earned from supplying customers that have the following characteristics: being aged between 46 and 55, having a household income of at least exteuro75,000 per annum, being self-employed, having a third level education, having a professional or managerial occupation, living in a household with 7 or more people, living in a detached house, having at least 5 bedrooms or being a mortgage holder. An OLS regression shows that gross margin is partly explained by the energy conservation measures which are present in a household, the number of household members, the number of bedrooms, income, age, occupation and accommodation type.
Keywords: 330; electricity demand; market segmentation; gross margin; Ireland